Heritage and globalisation - Labadi, Sophia; Long, Colin , 1966- (Routledge, 2010)
This volume analyses the politics, policy and practice of cultural heritage at the global level, identifying the major directions in which international heritage practice is moving and exploring the key issues likely to shape the cultural heritage field in the 21st century